Bioactive compounds and composition of Elaeis oleifera mesocarp oil extracted by hydraulic pressing - R. Antoniassi; A.E. Wilhelm; A.M.M. Guedes; A.F. Faria-Machado (Grasas y Aceites)
Elaeis oleifera oil has stood out for its high contents of carotenoids, tocochromanols, oleic and linoleic acids and low content of saturated fatty acids. The content of these bioactive compounds depends on the oil extraction process and the data available is related to solvent extraction. Pressing is the current industrial oil extraction process for palm fruits. E. oleifera bunches were harvested on two different days at an interval of two months. They were then sterilized and the fruits were submitted to hydraulic pressing and the oil from the mesocarp was evaluated. The main fatty acids of two samples were C18:1 (54.72 – 55.69%), C16:0 (23.72 – 24.23%) and C18:2 (15.47 – 16.95%). The alpha- and beta-carotene contents were 620-725 μg/g and 1,358– 1,403 μg/g, respectively. Gamma-tocotrienol accounted for 799 and 1,066 μg/g. The oil is a concentrate of pro-vitamin A and rich in gamma-tocotrienol and its low oil acidity allows for the consumption of the crude oil.